Global Rangelands Data Platform - Vizzuality (Vizzuality, 2024)
Presentation of the global rangelands data platform being developed by Vizzuality and GMV as a contribution to the GEF-funded IUCN implemented and ILRI executed project STELARR (Sustainable Investments for Large-Scale Rangeland Restoration).